2020
DOI: 10.1073/pnas.2014004117
|View full text |Cite
|
Sign up to set email alerts
|

Magnetized topological insulator multilayers

Abstract: We discuss the magnetic and topological properties of bulk crystals and quasi–two-dimensional (quasi-2D) thin films formed by stacking intrinsic magnetized topological insulator (for example, Mn (SbxBi1−x)2X4 with X = Se,Te) septuple layers and topological insulator quintuple layers in arbitrary order. Our analysis makes use of a simplified model that retains only Dirac cone degrees of freedom on both surfaces of each septuple or quintuple layer. We demonstrate the model’s applicability and estimate its parame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
2
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 50 publications
(84 reference statements)
7
60
2
1
Order By: Relevance
“…These edge states provide the electron density of states for the observation of the gapless surface state in the ARPES experiment. A similar explanation is also proposed, 52 in which the directions of surface magnetic moments change in different terraces (domains). Consequently, topological edge states occur at the step edges of different terraces.…”
Section: Puzzle Of Surface States Of Mbtsupporting
confidence: 56%
See 3 more Smart Citations
“…These edge states provide the electron density of states for the observation of the gapless surface state in the ARPES experiment. A similar explanation is also proposed, 52 in which the directions of surface magnetic moments change in different terraces (domains). Consequently, topological edge states occur at the step edges of different terraces.…”
Section: Puzzle Of Surface States Of Mbtsupporting
confidence: 56%
“…Another route to regulating the properties of MBT is element substitution. 52,[85][86][87] Both magnetic and carrier properties are tunable by substituting Sb for Bi, and thus topological effects can be controlled by changing the proportion of Sb atoms in Mn(Sb x Bi 1Àx ) 2 Te 4 . 85,86 Yan et al 85 reported that, with increasing Sb content in Mn(Sb x Bi 1Àx ) 2 Te 4 , the Néel temperature decreased slightly from 24 K for MnBi 2 Te 4 to 19 K for MnSb 2 Te 4 , while the critical magnetic field strengths required for spin-flop transition and moment saturation decreased dramatically.…”
Section: Chemically Substituted Mbtmentioning
confidence: 99%
See 2 more Smart Citations
“…was discovered [14][15][16][17] and attracted extensive interest [18][19][20][21][22][23][24][25][26].…”
mentioning
confidence: 99%